Epidemiology and evaluation of spine injuries in equestrian sports - Kłusek, Magdalena; Chawrylak, Katarzyna; Kuszneruk, Julia; Kubas, Maria; Krzemińska, Katarzyna (Quality in Sport, 2024)
Introduction and purposes: Severe injuries are a documented consequence of horse riding accidents. This study aims to explore the prevalence of spine injuries associated with horse riding, identify the most common types of injuries, examine mechanistic underpinnings, analyze typological manifestations, assess implicated spinal regions, investigate demographic risk factors, and examine ensuing neurological sequelae and back pain. Materials and Methods: A systematic literature search was conducted using PubMed and Google Scholar. The search employed terms such as 'horse riding,' 'injuries,' 'spine,' 'vertebral,' 'horse-related,' 'equestrian injuries,' 'spinal fractures,' and 'back injuries.' Articles published between 2014 and 2024 were included in the search. Results: The primary injury mechanism for horse riders is falling from a moving horse. Studies present conflicting findings on which parts of the spine are most commonly injured. Equestrian activities contribute significantly to sports-related spinal injuries, with spinal injuries ranking as the second most affected body region after head injuries among equestrians. Experienced riders tend to have fewer injuries compared to amateurs. Spine fractures are more prevalent in riders aged over 40 years, and a substantial majority (over 80%) of riders have experienced back pain at some point in their lives. Conclusion: In summary, horseback riding poses a substantial risk of spine injuries or pain. A thorough understanding of horse-related spine injury epidemiology is crucial for specific subgroups, enabling the development of preventive strategies across all levels of responsibility.